Smart Solar Ventilation System For Home Using Internet Of Things (IOT) - Ahmad Shukran, Ahmad Irfan (Progress in Engineering Application and Technology, 2023)
Industrial revolution 4.0 or IR4.0 has been widely applied at the current industrial level. By using today's technological facilities, users can monitor and control devices or equipment more efficiently and effectively. Related to this project, this exhaust fan is widely applied at home or around commercial buildings. So, the IoT system has been installed on this exhaust fan to make it easier for users to control and monitor the state of the device's open and close switch. Furthermore, with the use of renewable energy such as solar power, electricity can be supplied continuously without affecting the earth's ecosystem itself. In accordance with Malaysia's climate which is mostly hot, energy supply can be channeled continuously and efficiently. Therefore, this project is designed to make it easier for users to automatically monitor and control the condition of opening and closing the exhaust fan switch, especially in residential areas. In application, the temperature sensor will detect high temperature to automatically open the exhaust fan switch and close the switch when the temperature returns to normal. So, this can achieve the goal of IR4.0 to be applied in our daily life in order to keep up with the flow of technology today.